GAMBARAN SATURASI OKSIGEN PADA PENDERITA ASMA DI RSUD. Prof. Dr. SOEKANDAR MOJOSARI MOJOKERTO - M.Sajidin; Nur So?emah, Eka (JURNAL KEPERAWATAN SEHAT, 2015)
Oxygen saturation affects the cerebral blood flow (ADO) and intrakranial pressure. The background of this study is that in theory the organs in the body requires oxygen supply is sufficient in order to function optimally and effectively. If low oxygen saturation, many health problems can occur which occurred hypoxemia. Symptoms may include fatigue, confusion, headache, and shortness of breath that. Because oxygen is needed in the brain and heart constantly, brain damage or death can occur if the blood oxygen level is too low (Musliha, 2010). This research is descriptive. The study was conducted at Hospital Prof. Dr. Soekandar Mojosari Mojokerto, in May 2015 the number of respondents were 46 patients who met the inclusion criteria. Instrument data collection using observation sheets oxygen saturation. From the results, the oxygen saturation in patients with asthma as many as 28 people (59.6%) with abnormal oxygen saturation, as many as 19 people (40.4%) with normal oxygen saturation. Measurement of oxygen saturation is indicated when a patient falls into the possibility of respiratory failure and then requires more intensive management. The value of oxygen saturation through pulse oximetry obtained unreliable in a state of cardiac arrest, shock, use of medication vasokontriktor, administration by intravenous dye that colors the blood, severe anemia, and high carbon dioxide levels (Smeltzer and Bare, 2002). Picture oxygen saturation in patients wit asthma are mostly normal.Keywords: Oxygen Saturation